Risk Adjustment in Home and Community Based Services Outcome Measurement - Houseworth, James; Kilaberia, Tina; Ticha, Renata; Abery, Brian (Frontiers in Rehabilitation Sciences, 2022)
The purpose of this study was to review and evaluate existing research that used risk adjusters in disability research. Risk adjustment controls for individual characteristics of persons when examining outcomes. We have conducted a systematic review and an evaluation of existing studies that included risk adjusters for outcomes of people with disabilities receiving services (home or community based). The process included coding each study according to the type(s) of risk adjusters employed and their relation to the specific population and outcomes within a framework. Panels were utilized to prioritize the risk adjusters. Findings indicate that four risk adjusters can be tentatively recommended as potential candidate risk adjusters: chronic conditions, functional disability, mental health status, and cognitive functioning. Holistic Health and Functioning far outweighed other outcomes studied to date. Further, there is a need for testing recommended risk adjusters across multiple outcomes and different populations of people with disabilities.